Pengaruh Promosi Dan Distribusi Untuk Meningkatkan Nilai Penjualan Sepeda Motor Honda CRF Studi Kasus Pada Dealer Honda Mitra Sehati Jaya, Bandar Jaya - Lelawati, Nina; Riyanto, Kuncoro Budi; Septindo, Muhammad Andrean (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study is to find out whether interest has an effect on purchasing decisions for Honda Scoopy Motorcycles, to find out whether Lifestyle influences motorbike purchasing decisions. Honda Scoopy, knowing Brand Image has an effect on purchasing decisions for Honda Scoopy Motorcycles, and knowing Interest, Lifestyle and Brand Image have an effect on purchasing decisions for Honda Scoopy Motorcycles. The research method uses quantitative research that measures the variables of interest, lifestyle, brand image, and purchasing decisions. The population in this study were Honda Scoopy customers at TDM Honda Motor Sekampung. The instrument in this study used a questionnaire. Data analysis in this study used multiple linear regression. The results showed that the t-test value on the interest variable with a significance level of 5% was 0.005 <0.05 and tcount (2.96) > ttable (2.03), so that there was a positive and significant influence on interest. customers on purchasing decisions for Honda Scoopy motorcycles. The value of the t test on the lifestyle variable with a significance level of 5% is 0.034 < 0.05 and tcount (2.198) > ttable (2.03), so that there is a positive and significant influence on lifestyle on motorcycle purchasing decisions Honda Scoopy. The value of the t test on the brand image variable with a significance level of 5% is 0.007 < 0.05 and t (2.861) > t table (2.03), so that there is a positive and significant influence on brand image on motorcycle purchasing decisions Honda Scoopy. There is a positive and significant influence of interest, lifestyle, and brand image on purchasing decisions for Honda Scoopy motorcycle products at TDM Sekampung.